Diálogo e interdiscurso na literatura de autoajuda - (:unkn) unknown (Universidade Federal de Goiás, 2014)
The research "Dialogue and interdiscourse in self-help literature" aims at analyzing the interdiscursive and dialogical construction work on the book Você é insubstituível, written by Augusto Cury. The theoretical reflection is inscribed on the assumptions of discourse analysis from Michel Pêcheux ( 1997, 2002 , 2007, 2009 , 2011), focusing on the notions of subject and interdiscourse, also in dialogue with the philosophy of language from the Bakhtin Circle (1981, 2001, 2006 , 2011) on the theory of dialogism and the notion of subject. Pêcheux (2009), in dialogue with Foucault's theory, notes that the ideological formulations comprise the discursive formations (FD), thus resulting in the combination of different discourses, to what in Discourse Analysis, we call interdiscourse. These discourses that permeate the speech utterances are seized by linguistic materiality of events that are marked on the history and ideologies that transform and change in given language situations. In view of the Bakhtin Circle, discourse is not conceived as individual speech, but as significant instance in which other discourses - conveyed socio- historically and taking place in and by the interactions between subjects - intertwine and cross each other. In the analysis of discursive sequences, we found that the enunciator subject of self-help discourse who is presented on the book Você é insubstituível, appropriates various socially legitimated discourses as a way to validate his own speech. We focused our reflection on the analysis of capitalist, religious and scientific discourses once they are founder discourses that constitute the self-help discourse. Therefore, we seek from the corpus analysis identify interdiscursivity (other discourses) as well as the dialogues (the interaction between different words) in the book Você é insubstituível, as well as to analyze the production of meaning in the confrontation between the capitalist, religious and scientific discursivities in the constitution of self-help discourse.
Dialogue and interdiscourse in self-help literature
Keywords: Análise do discurso; Círculo de Bakhtin; Interdiscurso; Diálogo; Autoajuda; Discourse analysis; Bakhtin´s circle; Interdiscourse; Dialogue; Self-help; LINGUISTICA::FISIOLOGIA DA LINGUAGEM